2003
DOI: 10.1302/0301-620x.85b6.13972
|View full text |Cite
|
Sign up to set email alerts
|

Ligament repair and reconstruction in traumatic dislocation of the knee

Abstract: e treated 21 patients with 22 dislocations of the knee by repair or reconstruction of all injured ligaments. Eight knees were treated in the acute phase (less than two weeks after injury); the remainder were treated more than six months after injury (6 to 72). Reconstructions were carried out with a combination of autograft and allograft tendons and by direct ligament repair where possible. At a mean follow-up of 32 months (11 to 77) the mean Lysholm score was 87 (81 to 91) in the acute group and 75 (53 to 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
178
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 29 publications
8
178
3
6
Order By: Relevance
“…Those authors concluded staged reconstruction minimized postoperative stiffness. Their results confirmed the risk of arthrofibrosis and stiffness was higher when both cruciate ligaments were reconstructed at the same time [6,7,16,17,29,30]. This aspect was even more important when associated lesions, such as neurovascular injuries, or fractures occurred.…”
Section: Discussionmentioning
confidence: 73%
“…Those authors concluded staged reconstruction minimized postoperative stiffness. Their results confirmed the risk of arthrofibrosis and stiffness was higher when both cruciate ligaments were reconstructed at the same time [6,7,16,17,29,30]. This aspect was even more important when associated lesions, such as neurovascular injuries, or fractures occurred.…”
Section: Discussionmentioning
confidence: 73%
“…Existing knee dislocation studies focus on surgical treatment of the ligamentous injuries [1,8,[17][18][19]30], but the impact of associated injuries such as those to the popliteal artery or peroneal nerve can be just as vital. In this study, we evaluated motor and sensory recovery as well as patient-reported outcomes scores in patients with peroneal nerve injury after knee dislocation, compared recovery between partial and complete palsies, and established the impact of peroneal nerve injury by contrasting results with a cohort of patients without nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of surgical treatment was later shown to be more effective than conservative treatment [2,3]. It began with the primary repair of the injured ligaments [4][5][6], then evolved into the era of reconstruction [7][8][9][10][11][12][13][14][15][16][17][18]. Surgical reconstruction is now the standard of care for most patients, although good results were recently achieved with repair [4].…”
Section: Introductionmentioning
confidence: 99%